Kesiapan Sumber Daya Manusia dalam Menghadapi Implementasi Teknologi Digital: Studi Kebutuhan Pelatihan dan Pengembangan Kompetensi - Yuli Alam; M Bambang Purwanto (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid digital transformation demands that human resources (HR) be able to adapt to various new technologies in the workplace. This study aims to analyze the level of HR readiness in facing the implementation of digital technology, identify the required digital competencies, and develop relevant training strategies based on actual needs. The research method used was a quantitative descriptive approach with a survey of 120 respondents from the service and public administration sectors. The results show that HR readiness levels vary, with younger generations and operational workers showing higher readiness than senior generations and upper management positions. The most needed digital competencies include basic digital literacy, data analysis skills, utilization of work software, cybersecurity, and digital communication. The main implication of these findings is the need for initial competencies and the implementation of needs-based training to effectively address the challenges of digital transformation. Designed training programs must not only consider initial skill levels but also be tailored to the work context and individual roles within the organization. This adjustment aims to increase training effectiveness and accelerate the technology adaptation process. This study also identified implementation barriers, such as budget constraints, resistance to change, and lack of top management support. Therefore, a strong internal communications strategy is needed to build awareness of the urgency of digitalization, as well as a commitment from management to create a work ecosystem that supports the sustainable development of digital competencies. These findings provide an important contribution to developing adaptive and resilient HR development strategies in the digital era. Furthermore, cross-departmental collaboration is also necessary to create an inclusive and progressive digital work culture.